Pengembangan Sistem Pengendalian Lampu Otomatis Berbasis Deteksi Gerak dan Optimalisasi Konsumsi Energi Menggunakan Pendekatan IoT - Leli Donaningrum; Samuel Parlindungan Siringo-ringo; Desti Karmini Nurdatillah; Shinvi Nur Najmil Jannah; Cep Luthfi Rizky Fauzi; Muhamad Arbi Nur Wulan Tumanggal (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research aims to design and develop a motion detection-based automatic light control system with a light intensity setting feature using IoT technology. The system utilizes a combination of PIR sensor, MOSFET module, and Arduino Uno microcontroller to control lighting based on the presence and position of the user. With an adaptive control algorithm, the lamp can dynamically adjust the lighting intensity to several levels as needed. Test results show that the system successfully reduces energy consumption optimally without reducing user comfort. The implementation of this technology has great potential in supporting energy efficiency in public areas, such as parks, office hallways, and sidewalks.